Manufacturing Companies :The Effect of Liquidity and Corporate Governance on Financial Performance with Firm Size as a Moderating - Dyana Novita Taristy; Ulil Hartono; Nadia Asandimitra Haryono (Profesional Muda Cendekia Publishing, 2022)
Financial performance is important to see the level of achievement of predetermined targets, as material for evaluation, and policies that must be taken by management. The influence of liquidity and good corporate governance through the mechanism of ownership structure towards the financial performance of Manufacture Company listed on the IDX in 2020-2021 with firm size as moderating variable are the aim of this research. This type of research is quantitative research with secondary data. The purposive sampling method was used for research sampling and obtained 87 companies. Moderate regression analysis (MRA) is used to be analysis technique in this research. This research get results that liquidity has a significant positive effect on financial performance, but institutional and managerial ownership have not effect on financial performance because companies whose ownership structure is dominated by institutional investors actually get a poor response from the market and the company's managerial shareholding has not been able to align the interests of shareholders outside of management, and then firm size can’t moderate the relationship of liquidity, institutional and managerial ownership to financial performance because the size of the company is not so much noticed by interested parties in the company.